2002
DOI: 10.2337/diacare.25.5.876
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Insulin Aspart and Biphasic Insulin Aspart in People With Type 1 and Type 2 Diabetes

Abstract: OBJECTIVE -The antibody responses to a novel rapid-acting insulin analog, insulin aspart (IAsp), and their potential clinical correlates were studied with a specifically developed method in 2,420 people with diabetes treated for up to 1 year with preprandial subcutaneous injections of IAsp. RESEARCH DESIGN AND METHODS -Circulating insulin antibodies were analyzed by radioimmunoassay with 125I insulin or IAsp tracers and polyethylene glycol precipitation. Four multinational, open, parallel group studies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 17 publications
10
73
3
Order By: Relevance
“…The increase in antibodies in this study is consistent with those seen in long-term insulin analog trials where no effects on efficacy and safety could be attributed to changes in antibody levels (23,24). Increased insulin antibody serum binding, with no apparent clinical changes, has also been observed with another inhaled insulin device (25,26), as well as with treatment with implantable insulin pumps (27).…”
Section: Safetysupporting
confidence: 74%
“…The increase in antibodies in this study is consistent with those seen in long-term insulin analog trials where no effects on efficacy and safety could be attributed to changes in antibody levels (23,24). Increased insulin antibody serum binding, with no apparent clinical changes, has also been observed with another inhaled insulin device (25,26), as well as with treatment with implantable insulin pumps (27).…”
Section: Safetysupporting
confidence: 74%
“…Our results, which suggest that insulin antibodies do not develop during pregnancy when using either IAsp or HI, are reassuring and comparable to previous data involving non-pregnant participants with type 1 and type 2 diabetes [6] and those with gestational diabetes mellitus treated with IAsp or insulin lispro [8,9]. Overall, there was a small reduction in cross-reacting insulin antibodies in the IAsp group, perhaps similar to the decrease in levels seen with other types of antibody during pregnancy, such as serum antithyroglobulin [10].…”
Section: Discussionsupporting
confidence: 78%
“…Laboratory analyses Antibody analyses were performed by MDS Pharma Services (Fehraltorf, Switzerland) using a RIA method [6]. The results are expressed as the percentage of bound radioactivity relative to the total.…”
Section: Methodsmentioning
confidence: 99%
“…Structural changes leading to insulin lispro and insulin aspart (monomeric insulins) were initially reported to result in decreased immunogenicity in in vivo studies [17,18]. However, recent studies with both insulin lispro [42,43] or insulin aspart [44] rather reported results supporting similar immunogenicity of the two analogues when compared to human regular insulin. A multinational, multicentre combination of controlled and non-controlled, open-label studies of 4.5 years' duration showed that the incidence of insulin allergy in patients receiving subcutaneous administration of insulin lispro was not different from that in patients treated with recombinant regular human insulin [42].…”
Section: Insulin Analogues and Insulin Allergymentioning
confidence: 71%
“…A multinational, multicentre combination of controlled and non-controlled, open-label studies of 4.5 years' duration showed that the incidence of insulin allergy in patients receiving subcutaneous administration of insulin lispro was not different from that in patients treated with recombinant regular human insulin [42]. Lindholm et al [44] reported that insulin aspart caused allergic reactions as frequently as regular human insulin, although there was no consistent relationship between antibody formation and adverse events.…”
Section: Insulin Analogues and Insulin Allergymentioning
confidence: 99%